Exploring Careers in Cybersecurity and Digital Forensics - Tsado, Lucy K.; Osgood, Robert (Rowman & Littlefield Publishers, 2022)
Exploring Careers in Cybersecurity and Digital Forensics is a one-stop shop for students and advisors, providing information about education, certifications, and tools to guide them in making career decisions within the field. Cybersecurity is a fairly new academic discipline and with the continued rise in cyberattacks, the need for technological and non-technological skills in responding to criminal digital behavior, as well as the requirement to respond, investigate, gather and preserve evidence is growing. Exploring Careers in Cybersecurity and Digital Forensics is designed to help students and professionals navigate the unique opportunity that a career in digital forensics and cybersecurity provides. From undergraduate degrees, job hunting and networking, to certifications and mid-career transitions, this book is a useful tool to students, advisors, and professionals alike. Lucy Tsado and Robert Osgood help students and school administrators understand the opportunity that exists in the cybersecurity and digital forensics field, provide guidance for students and professionals out there looking for alternatives through degrees, and offer solutions to close the cybersecurity skills gap through student recruiting and retention in the field.